2021
DOI: 10.4254/wjh.v13.i12.2071
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte cell-derived chemotaxin-2 and fibroblast growth factor 21 in alcohol-induced liver cirrhosis

Abstract: BACKGROUND The importance of early diagnosis of alcoholic liver disease underscores the need to seek better and especially non-invasive diagnostic procedures. Leukocyte cell-derived chemotaxin-2 (LECT2) has been widely studied to determine its usefulness in monitoring the course of non-alcoholic fatty liver disease but not for alcoholic liver cirrhosis (ALC). AIM To determine the concentration of LECT2 in the blood serum of patients in relation to progressive stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Taohong Siwu Decoction, a popular TCM formulation used for activating blood circulation and removing blood stasis, has been widely used in clinics. The present study was focused on the influence of Taohong Siwu Decoction on the recurrence of AAP, and its possible mechanism [15]. In the treatment group, serum amylase level was gradually decreased until it returned to normal, and the pancreatic histopathological score and col Ⅰ content were also significantly decreased.…”
Section: Discussionmentioning
confidence: 97%
“…Taohong Siwu Decoction, a popular TCM formulation used for activating blood circulation and removing blood stasis, has been widely used in clinics. The present study was focused on the influence of Taohong Siwu Decoction on the recurrence of AAP, and its possible mechanism [15]. In the treatment group, serum amylase level was gradually decreased until it returned to normal, and the pancreatic histopathological score and col Ⅰ content were also significantly decreased.…”
Section: Discussionmentioning
confidence: 97%
“…Another study also found that LECT2 induces the development of NAFLD by mediating the phosphorylation level of STAT-1 and the expression of its downstream genes cluster of differentiation 36 (Cd36), chemokine (C-X-C motif), ligand 10 (Cxcl10), and unc-51-like autophagy-activating kinase 1 (Ulk1) ( 7 ). In addition, LECT2 is also reported as a non-invasive diagnostic factor for alcohol-induced liver cirrhosis ( 9 ).…”
Section: The Roles Lect2 In Immune Diseasesmentioning
confidence: 99%
“…LECT2 is also identified as a hepatokine. Hepatocyte-derived LECT2 not only regulates hepatocyte cells in an autocrine mode, but can also be secreted into the bloodstream to act on cells of other tissues in a paracrine way to modulate multiple metabolic homeostasis or disorders such as glucose metabolism, non-alcoholic fatty liver disease (NAFLD) ( 7 , 8 ), alcohol-induced liver cirrhosis ( 9 ), obesity ( 10 ), diabetes ( 11 , 12 ), and atherosclerosis ( 13 ). LECT2 is also positively correlated with diet-induced weight cycling in mice and humans, suggesting that LECT2 is a sensing hepatokine for nutritional regulation-mediated metabolic homeostasis and functions as an indicator for management of obesity in the clinic ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when acting as a direct biomarker to predict liver fibrosis in patients ( n = 147) with CHB (chronic hepatitis B), LECT2 was superior to the most common noninvasive scoring systems such as APRI (aspartate aminotransferaseto‐platelet ratio index) and FIB‐4 (fibrosis index based on the four factors). However, Sak et al 19 observed that the level of LECT2 in patients with alcohol‐induced liver cirrhosis decreased with the progression of cirrhosis. The concentrations of serum LECT2 decreased to 11.06 ± 6.47 ng/ml in the Pugh‐Child A + B group ( n = 37 p < 0.0001), then dropped to 8.06 ± 5.74 ng/ml in the Pugh‐Child C group ( n = 32 p < 0.0001), compared with the control group (18.99 ± 5.36 ng/ml n = 17).…”
Section: Introductionmentioning
confidence: 99%
“…Sak et al19 observed that the level of LECT2 in patients with alcoholinduced liver cirrhosis decreased with the progression of cirrhosis.…”
mentioning
confidence: 99%